Cyfluthrin and Deltamethrin Induce Changes in the Fat Body Composition of Tenebrio molitor Larvae, Males and Females. Issue 5 (2nd May 2019) - Wojciechowska, Marta; Stepnowski, Piotr; Gołębiowski, Marek
Abstract: The purpose of present study was to analyze the chemical composition of the fat body of insects ( Tenebrio molitor ) and its eventual variation after the application of insecticides. Using the GC/MS technique, the fat body composition of larvae, males and females was analyzed. The insects were stressed with selected insecticides containing cyfluthrin (Cyflok 50EW) and deltamethrin (K‐othrine) recommended for this species of insect by insecticides producers and farmers. The effect of these two chemicals on the chemical compounds patterns from fat body of insects was compared. Possible differences in the fat body composition between developmental stages and the sex of insects were also compared. Possible identified compounds included amino acids, carboxylic acids, alcohols, sterols, glycerol and urea. Our results show that the composition of lipids was different depending on the stage of development, the insecticide used and the elapsed time since its application. Abstract :